INDIGENOUS KNOWLEDGE AND SOCIOECONOMIC VALUES OF THREE KOLA SPECIES (COLA NITIDA, COLA ACUMINATA AND GARCINIA KOLA) USED IN SOUTHERN BENIN - Durand, Dah-Nouvlessounon; Hubert, Adoukonou-Sagbadja; Nafan, Diarrassouba; Adolphe, Adjanohoun; Farid, Baba-Moussa; Alphonse, Sezan; Lamine, Baba-Moussa (European Scientific Journal, ESJ, 2015)
This research paper aims to study the ethnobotanical knowledge and evaluate the socio-economic potentials of the three different kola species (Cola nitida, Cola acuminata and Garcinia kola) used in southern Benin. Some semi structured and semi quantitative surveys were made with 461 people from 62 villages and 13 main-markets. The study revealed that, those interviewed were conversant with the three kola species, though with varying level of knowledge. This knowledge depends on the cultural ties of each ethnic group to the specie. Some morphotypes were traditionally recognized in C. nitida and C. acuminata through their nuts’ colors. Other information related to the use as well as to the socio-cultural importance of kola trees were also registered. The analysis of the market revealed a substantial variation of the purchase and sale average prices. C. acuminata had the highest economic value with a selling price of 64.78±16.16 Euro/ 25 kg of nuts (producer). It is followed by C. nitida (49.54±10.77 Euro/ 25 kg of nuts) and G. kola (24.01±4.85 Euro/ 25 kg of nuts). This study revealed the social and cultural importance, the medicinal benefits and the economic potentials of kola genetic resources in the southern part of Benin. The valorization of these species will help to keep them and at the same time increase the income of the local people.